1994
DOI: 10.1063/1.467658
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Doppler laser spectroscopy of the 1B2(1Δu) state of CS2 in a cold molecular beam

Abstract: Direct observation of the (2) 3Π u state of Cs2 by resonance enhanced two photon ionization spectroscopy in a very cold molecular beam J. Chem. Phys. 99, 5677 (1993); 10.1063/1.465936 Dopplerfree high resolution laser spectroscopy of the Cs2 D 1Σ+ u state and the predissociation J. Chem. Phys. 94, 2600 (1991); 10.1063/1.460690SubDoppler laser spectroscopy of SO2 in a supersonic beam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Therefore, the new lines can be identified as transitions that become allowed by the magnetic field induced perturbation with the upper level V 1 B 2 (vЈ;03M ) of the P͑4͒ and R͑2͒ lines. This was first observed by Habib et al 10 Our spectrum is, however, superior in both sensitivity and resolution, which allows the unambiguous assignment of M . This assignment and accordingly the interpretation of the Zeeman pattern differs from that proposed by Habib et al 11 as will be shown below.…”
Section: Analysis and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, the new lines can be identified as transitions that become allowed by the magnetic field induced perturbation with the upper level V 1 B 2 (vЈ;03M ) of the P͑4͒ and R͑2͒ lines. This was first observed by Habib et al 10 Our spectrum is, however, superior in both sensitivity and resolution, which allows the unambiguous assignment of M . This assignment and accordingly the interpretation of the Zeeman pattern differs from that proposed by Habib et al 11 as will be shown below.…”
Section: Analysis and Discussionmentioning
confidence: 52%
“…High-resolution spectroscopy was first applied to study the magnetic field effect on the 1 B 1 state of pyrimidine. 7 Recently, Zeeman spectra of the V system of CS 2 were measured parallel and independently by Katô et al 8,9 and by Habib et al 10,11 Habib et al found a new transition to appear close to the P͑4͒ line, and they identified the rotational quantum number of the upper level to be JЈϭ3. We also independently observed the same phenomena.…”
Section: Introductionmentioning
confidence: 98%
“…Effectively, the highresolution excitation spectrum of the 15V near the P(2) transition has been achieved in a supersonic jet. 8 From this study, it appears that five transitions near the P(2) should have been excited by our 3 GHz bandwidth laser. The most important one is at 300 MHz from the P(2), but it is not identified by the authors.…”
mentioning
confidence: 68%
“…Up to five other electronic states could interact with the 1 B 2 state. 8 In the rotational analysis of the 10V band of the 1 B 2 state ͑the band just below the 15V͒, up to four transitions with the same value of J have been assigned. 9 The anarchy of the rotational bands of the 1 B 2 state explains the possibility to find a P(2) in coïncidence with a R(10).…”
mentioning
confidence: 99%
“…For the depicted LIF and DFWM data sets, the excitation frequency of the high-resolution (Շ0.05 cm Ϫ1 ultraviolet bandwidth͒ dye laser was tuned into resonance with the prominent R(6) rotational line of the CS 2 V 1 B 2 ( 1 ⌬ u )←X 1 ͚ g ϩ 10 V band at 30 903.023 cm Ϫ1 . 26 Although extensive spectroscopic perturbations have been documented, [26][27][28][29] features in this region are assigned nominally 27 to the (000) Kϭ0 Ϫ(00 0 0) origin band of the V ϪX (*←) absorption system. The intensities of fluorescence and four-wave mixing signals emerging from the interaction volume were monitored as the time interval between the nozzle-actuating current pulse and the interrogating optical pulse was scanned electronically.…”
Section: Fabrication and Operationmentioning
confidence: 99%